APPLICATION OF COGNITIVE BEHAVIOR COUNSELING IN HELPING HANDLING THE CRISIS OF IDENTITY OF CLASS VIII STUDENTS OF STATE MIDDLE 1 BANYUWANGI - Jawahirul Kawakib; Atim Hariyadi (SOSIOEDUKASI, 2020)
This research aims to help deal with the identity crisis experienced by VIII grade students of SMP Negeri 1 Banyuwangi. The research carried out is a guidance and counseling action research in which the research was carried out in two cycles. The subjects consisted of five classes, each consisting of 30 students so that the total number was 150 people. There are nine students who show the behavior of adolescents who experience identity crisis seen based on the percentage of the results of the questionnaire and direct observation, and the nine students are given the form of cognitive behavioral counseling. In this study, in the first cycle an increase was obtained, but only two students achieved criteria above 80%, while seven students had not achieved a significant improvement. So that the second cycle is held, the overall student reaches an increase of up to 80% and above. The results of the analysis showed that the effort to overcome the identity crisis experienced by students by using cognitive behavioral counseling services in eighth grade students of SMP Negeri 1 Banyuwangi, there was a change in student behavior toward more positive individuals and groups